Pehitungan Harga Pokok Produksi Pada Pt Lentera Abadi Surakarta - Arifa Nur Azizah; Sulistiyo Sulistiyo (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
This Final Project aims to calculate the cost of production by the cost of order method on the end table product order and carved table and compare the results of PT Lentera Abadi Surakarta with the results of the study. The data used are primary data and secondary data including data about production cost determination conducted by PT Lentera Abadi Surakarta, and also company overview. Data collection methods use in this Final Project is interview, observation and documentation. Based on calculations and analysis that have been done, there is a difference in cost of production of the company by the job order costing method on the order end table amounting to Rp 27.512 and carved table orders of Rp 85.988. This difference occurs because in calculating the cost of production the company incorporates marketing costs, administrative and general costs into the components of factory overhead costs and not include PBB cost.